Diagnostic accuracy study of the VALENF instrument in hospitalization units for adults: a study protocol - Víctor M. González-Chordá; David Luna Aleixos; Irene Llagostera Reverter; Àgueda Cervera-Gash; Francisco Herrero Machancoses; María Teresa Moreno-Casbas; Patricia Flor Arasil; María Jesús Valero Chillerón (BMC, 2023)
Abstract Recently, the VALENF instrument, Nursing Assessment by its acronym in Spanish, was developed as a meta-tool composed of only seven items with a more parsimonious approach for nursing assessment in adult hospitalization units. This meta-tool integrates the assessment of functional capacity, the risk of pressure injuries and the risk of falls. The general objective of this project is to validate the VALENF instrument by studying its diagnostic accuracy against the instruments commonly used in nursing to assess functional capacity, the risk of pressure injuries and the risk of falls. An observational, longitudinal, prospective study is presented, with recruitment and random selection based on admissions to six adult hospitalization units of the Hospital Universitario de La Plana. The study population will be made up of patients hospitalized in these units. The inclusion criteria will be patients over 18 years of age with a nursing assessment within the first 24 h of admission and an expected length of stay greater than 48 h and who sign the informed consent form. The exclusion criteria will be transfers from other units or centers. A sample of 521 participants is estimated as necessary. The evaluation test will be the VALENF instrument, and the reference tests will be the Barthel, Braden and Downton indices. Sociodemographic variables related to the care process and results such as functional loss, falls or pressure injuries will be collected. The evolution of functional capacity, the risk of falls and the risk of pressure injuries will be analyzed. The sensitivity, specificity and positive predictive values of the VALENF instrument will be calculated and compared to those of the usual instruments. A survival analysis will be performed for pressure injuries, falls and patients with functional loss. The VALENF instrument is expected to have at least the same diagnostic validity as the original instruments. Trial registration The study will be retrospectively registered (ISRCTN 17699562, 25/07/2023).